MENGOPTIMALKAN LITERASI ALQURAN: MENGEKSPLORASI STRATEGI PEDAGOGIS DAN FAKTOR-FAKTOR SOSIAL-LINGKUNGAN YANG BERDAMPAK PADA KEMAHIRAN MEMBACA AL-QURAN DI KALANGAN SISWA MADRASAH TSANAWIYAH AL-IHSAN TANAH GROGOT - Annisa Mae Dilla (CV. ADIBA AISHA AMIRA, 2023)
This research was conducted because it is important for each individual to have the ability to read the Qur'an, as well as learn and understand the laws of reciting the Qur'an, but in reality there are still students who have not been able to read the Qur'an. Because of that, it is necessary to conduct research with the aim of knowing the Efforts of Al-Qur'an Hadith Teachers in Improving Al-Qur'an Reading Ability of Grade VIIB Students of Mts Al-Ihsan Tanah Grogot and the Factors that influence improving Al-Qur'an reading skills' an Shiva class VIIB Mts Al-Ihsan Tanah Grogot. This research is qualitative research, the instruments used in data collection are: observation, interviews and documentation. The data analysis used is data processed by qualitative analysis by going through the stages of data reduction, data display and conclusions. Based on the results of the research and analysis it was concluded that the efforts of the Al-Qur'an Hadith teachers to improve students' Al-Qur'an reading skills were by frequently reading the Al-Qur'an repeatedly and understanding the contents contained in the Al-Qur'an and pay attention to every tajwid reading in the Qur'an. And the factors in improving students' Al-Qur'an reading skills, namely the supporting and inhibiting factors are parental support and support from the surrounding environment.